2022
DOI: 10.1149/10908.0003ecst
|View full text |Cite
|
Sign up to set email alerts
|

(Invited) Recent Progress in Wide-Bandgap Semiconductor Devices for a More Electric Future

Abstract: Wide-bandgap (WBG) semiconductors, with their excellent electrical properties, offer breakthrough performance in power electronics enabling low losses, high switching frequencies, and high temperature operation. WBG semiconductors, such as silicon carbide and gallium nitride, are likely candidates to replace silicon in the near future for high power applications as silicon is fast approaching its performance limits. Wide-bandgap power semiconductor devices enable breakthrough circuit performance and energy eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The output signals, as exhibited in Figure b–e, for 50 Hz, 100 Hz, 500 Hz, and 1 kHz, were captured at 293 K environment by an oscilloscope (Tektronix MDO34). The obvious elongated recovery time of the photocurrent is known as the persistent photoconductivity (PPC) effect, which is mostly attributed to the numerous defect-induced trap states in the device. , This universally observed PPC effect severely limits the response speed in GaN-based optoelectronic devices. It has been reported that elevated temperatures can accelerate atom migration and therefore promote carrier collection to suppress the PPC effect. ,,, However, it brings drawbacks as an additional heating unit with extra power consumption is required. Fortunately, in this work, arising from the narrow fin width, the drift length of the photocarriers is shortened, and carriers can reach high velocity at a low bias voltage.…”
Section: Resultsmentioning
confidence: 99%
“…The output signals, as exhibited in Figure b–e, for 50 Hz, 100 Hz, 500 Hz, and 1 kHz, were captured at 293 K environment by an oscilloscope (Tektronix MDO34). The obvious elongated recovery time of the photocurrent is known as the persistent photoconductivity (PPC) effect, which is mostly attributed to the numerous defect-induced trap states in the device. , This universally observed PPC effect severely limits the response speed in GaN-based optoelectronic devices. It has been reported that elevated temperatures can accelerate atom migration and therefore promote carrier collection to suppress the PPC effect. ,,, However, it brings drawbacks as an additional heating unit with extra power consumption is required. Fortunately, in this work, arising from the narrow fin width, the drift length of the photocarriers is shortened, and carriers can reach high velocity at a low bias voltage.…”
Section: Resultsmentioning
confidence: 99%